2015
DOI: 10.1002/anie.201502930
|View full text |Cite
|
Sign up to set email alerts
|

Diastereodivergent Asymmetric 1,4‐Addition of Oxindoles to Nitroolefins by Using Polyfunctional Nickel‐Hydrogen‐Bond‐Azolium Catalysts

Abstract: Diastereodivergency is a challenge for catalytic asymmetric synthesis. For many reaction types, the generation of one diastereomer is inherently preferred, while the other diastereomers are not directly accessible with high efficiency and require circuitous synthetic approaches. Overwriting the inherent preference by means of a catalyst requires control over the spatial positions of both reaction partners. We report a novel polyfunctional catalyst type in which a Ni(II) -bis(phenoxyimine) unit, free hydroxy gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 38 publications
(16 reference statements)
1
29
0
Order By: Relevance
“…Peters designed polyfunctional catalysts equipped with a Ni II ‐bis(phenoxyimine) unit, free OH groups and an axially chiral bisimidazolium moiety to promote the enantioselective 1,4‐addition of oxindoles to nitroolefins (Scheme ) . It was proposed that the metal Ni activated the oxindole enolization by a bidentate coordination of carbonyl groups to the Ni, and the free hydroxy groups might determine the stereocenter generated at the oxindole.…”
Section: Ligand‐controlled Diastereodivergencymentioning
confidence: 99%
“…Peters designed polyfunctional catalysts equipped with a Ni II ‐bis(phenoxyimine) unit, free OH groups and an axially chiral bisimidazolium moiety to promote the enantioselective 1,4‐addition of oxindoles to nitroolefins (Scheme ) . It was proposed that the metal Ni activated the oxindole enolization by a bidentate coordination of carbonyl groups to the Ni, and the free hydroxy groups might determine the stereocenter generated at the oxindole.…”
Section: Ligand‐controlled Diastereodivergencymentioning
confidence: 99%
“…As a powerful strategy for addressing this intrinsic problem, catalyst-directed diastereodivergence would be much sought after. Impressive progress has been made in the development of diastereodivergent asymmetric catalysis for carbon–carbon and carbon-heteroatom bond-forming reactions234567891011121314151617181920212223242526272829303132. However, most of the processes currently available rely on using each elaborated catalyst, or the appropriate combination of two different catalysts, to access complementary diastereomers selectively.…”
mentioning
confidence: 99%
“…[8] Established strategies succeeded in the diastereocontrolledc onstruction of vicinal stereocenters by combining imiunium and enaminea ctivation of a,b-unsaturated systems. [11] Furthermore, by simple use of the optimized bifunctional Brønsted bases andt heir (pesudo)enantiomers, this multifunc-tional catalytic strategyc ould realize the stereocontrolled synthesis of 4d iastereomers out of 16 possible stereoisomers of the products with four contiguous stereocenters and ah igh degree of diastero-and enantiocontrol. [10] We found that the diastereoselectivity of the all-carbon [4+ +2] cyclizations of a-aryl a,b-unsaturated aldehydes and nitroolefins could be switched on (Scheme 1b)b yi ntroducing as econd steric control factor to the similart ype of bifunctional Brønsted base catalysts together with the optimized solvent.…”
mentioning
confidence: 99%
“…Catalyst II and Dixon's superbase III exhibited enforced enantioinduction with comparable activity and diastereoselectivity (Table 1, entries 2a nd 3). Further solvent, catalyst loading, and temperature screening revealed that the catalyst VII gave satisfactory resultsi nD CM with 4aa as the major diastereomer (Table 1, entries [10][11][12][13][14].Ad iastereodivergent synthesis study suggested that although the catalyst IX wase xploited, the reaction gave the product with 3aa as the major diastereomer in THF (Table 1, entries 15-18). [13] Investigation of multifunctional Brønsted base VIII and IX offered similar yields and enantioselectivities,a lbeit with lower diastereocontrol (Table 1, entries8and 9).…”
mentioning
confidence: 99%
See 1 more Smart Citation